Financial Performance and Firm Value Lesson from Mining Sub-sector Companies on the Indonesia Stock Exchange - Setiawanta, Yulita; Purwanto, Agus; Hakim, Much Azizum (Jurnal Dinamika Akuntansi, 2019)
This study aims to provide an overview of investor behavior on the current condition of the capital market in Indonesia and want to examine signal information about financial performance and prove directly the relation to firm value. This research was conducted on the issuer of mining sub-sector companies that has been listed in Indonesia Stock Exchange from 2015 to 2018. Using purposive sampling this research get 100 data observed. The data obtained were analyzed using multiple linear regression with PLS SEM statistical tools. We found that capital structure and profitability affect the firm value, but not for asset growth. Thus, it can be concluded that if two of three hypotheses accepted, can be interpreted that the signal information of financial performance from sample still hold interesting by an investor in the Indonesian Capital Market.